Assessing the Impact of Social Determinants on COVID-19 Vaccination Rates in Underserved Communities - Al-Mansouri, Yasmin H. (Magenta Journal De Healthymedi, 2024)
The COVID-19 pandemic has exposed significant disparities in vaccination rates, particularly among underserved communities. This study explores the impact of social determinants of health, including income, education, and healthcare access, on COVID-19 vaccination uptake in marginalized populations. Using a cross-sectional design, data were collected from 100 individuals across different socioeconomic backgrounds to assess vaccination behavior. The results demonstrate that individuals with higher income, better education, and greater healthcare access had significantly higher vaccination rates, while those facing economic hardship and limited healthcare access were less likely to be vaccinated. The study highlights the need for targeted public health interventions that address structural barriers and misinformation to improve vaccine equity. Recommendations include expanding healthcare access in underserved areas, enhancing health literacy, and building trust through culturally sensitive outreach. Addressing these factors is crucial for reducing health disparities and ensuring a more equitable public health response.